Experiences of residents, family members and staff in residential care settings for older people during COVID‐19: A mixed methods study. (20th March 2022) - Sweeney, Mary Rose; Boilson, Andrew; White, Ciara; Nevin, Mary; Casey, Briege; Boylan, Patrick; Staines, Anthony
Abstract: Aim: The aim of this study was to explore the COVID‐19 pandemic as it was experienced by people on the front line in residential care settings for older people in the Republic of Ireland (ROI). Background: The COVID‐19 pandemic had a disproportionate effect in residential care settings for older people in Ireland. Methods: A two‐phased mixed methods study was conducted, consisting of an online survey administered shortly after the first wave of the virus to staff, residents and family members and one‐to‐one interviews with family members shortly after wave 2 of the virus. Results: Isolation, loss of connectedness as well as a reduction in the level/quality of care provision led to significant adverse impacts for both residents and their families. Staff reported high levels of stress, trauma and burnout. Family input to care was suspended, with adverse consequences. Conclusion: The pandemic had an extremely adverse impact on residents, family members and staff in care settings for older people. Implications for Nursing Management: Strategies to ensure that residents' physical, emotional and social needs and staffs' professional and personal needs are appropriately supported during future waves of the pandemic should now be implemented.